The Quality Of Village-Owned Enterprises’ Financial Statement - Rini Indahwati; Nurlinda; Asmalidar (Jurnal Akuntansi, 2023)
The aim of this research is to reveal the variables that will influence the quality of village-owned enterprises’ financial statements in North Sumatra. This research defined 3 (three) variables that will influence the quality of village-owned enterprise’s financial statements: information technology, competency, and top management support. The research method for this research was quantitative mixed with the qualitative method. The data collection method was a survey with questionnaires. The population of this research was all the village-owned enterprises in North Sumatra. The random sampling method chose the sample for 33 (thirty-three) village-owned enterprises. The result of this research showed that information technology and competency did not affect the quality of the village-owned enterprises in North Sumatra. Top-management support was the variable affecting the quality of the village-owned enterprises in North Sumatra.